Capital Structure Choice in Emerging Markets: Do Business Cycles Matter? - Мария Сергеевна Кокорева; Михаил Сергеевич Никифоров (Journal of Corporate Finance Research / Корпоративные Финансы | ISSN: 2073-0438, 2015)
Kokoreva Maria Sergeevna - assistant professor, lecturer, HSE Higher School of Economics, deputy head of the school of finance, researcher of the scientific and educational laboratory of corporate finance, director of the joint educational program for the preparation of bachelors in the direction of "Economics" USU and HSE. E-mail: maria_kokoreva@mail.ruMikhail Sergeevich Nikiforov - National Research University "Higher School of Economics".E-mail: nikiforov.ms@gmail.comThis article presents the results of a study of corporate capital structure in emerging capital markets, taking into account the business cycles of the economy. Our study was conducted on the data of 581 companies from BRICS countries for the years 2002–2014. We revealed that the target capital structure is dependent on set of factors which is the same for both periods of economic growth and recession. The speed of adjustment to the target capital structure is dependent upon the stage of the business cycle of the economy and is higher for in economic growth periods. The study also found out that the direction of the impact of the determinants of the speed of adjustment varies depending on the state of the economy (the deviation from the target capital structure leads to an increase in the speed of adjustment in periods of growth and a fall - in times of recession).